2017
DOI: 10.12659/msm.905130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Connexin43 Overexpression on U251 Cell Growth, Migration, and Apoptosis

Abstract: BackgroundGlioblastoma multiforme (GBM) is a highly aggressive malignant brain tumor with a high incidence in adults. Connexin43 (Cx43) has general roles in tumorigenesis and is expressed in U251 glioma cells. Accordingly, the effects of Cx43 on the growth, migration, and apoptosis and the underlying mechanisms mediating Cx43-dependent migration and apoptosis were examined in U251 cells.Material/MethodsA Cx43-overexpressing U251 cell line was generated to analyze the effects of Cx43 overexpression on cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…24 The U251 glioblastoma cell line has been selected due to its endogenous expression of functional Cx43 GJs. 25,26 The assay was validated using previously published GJ inhibitors such as MEF, quinidine, or niflumic acid, 17,27,39,40 whereas carbenoxolone did not display any inhibition in this setup. Those drugs present different mechanisms of action, as for instance carbenoxolone acts by modulating protein kinase Adependent pathway 41 and MEF through interference with loop gating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The U251 glioblastoma cell line has been selected due to its endogenous expression of functional Cx43 GJs. 25,26 The assay was validated using previously published GJ inhibitors such as MEF, quinidine, or niflumic acid, 17,27,39,40 whereas carbenoxolone did not display any inhibition in this setup. Those drugs present different mechanisms of action, as for instance carbenoxolone acts by modulating protein kinase Adependent pathway 41 and MEF through interference with loop gating.…”
Section: Discussionmentioning
confidence: 99%
“…24 U251 glioblastoma cells were selected due to their expression of functional Cx43 GJs. 25,26 Screening of the Prestwick Chemical Library Ò (PCL; 1,280 compounds) that mostly contains approved drugs (or compounds under preclinical and clinical development) led to the identification of new classes of Cx43 inhibitors. Some of those newly identified inhibitors were previously described as modulators of microtubules dynamics strongly suggesting that GJs function requires a proper microtubule cytoskeleton network.…”
mentioning
confidence: 99%
“…It was previously demonstrated that Cx43 reduces the sensitivity of human LN18 and LN229 glioma cells to TMZ by reducing the Bax/Bcl-2 ratio and the release of cytochrome c ( 29 ). Overexpression of Cx43 promotes the migration of U251 cells and inhibits apoptosis by upregulating Bcl-2 and downregulating the expression of Bax and caspase-3 ( 46 ). Thus, the effect of rExo on the expression of Bcl-2, Bax and cleaved caspase-3 in U251s cells was examined.…”
Section: Discussionmentioning
confidence: 99%
“…There are at least two plausible explanations for the role of exosomal Cx43 in the resistance of glioma cells to TMZ. First, the exosomal Cx43 may enhance TMZ resistance through modulating the expression of the pro-apoptotic and anti-apoptotic proteins and inhibiting the intrinsic apoptosis pathway ( 29 , 46 ). Second, high expression of Cx43 in rExo may contribute to the formation of gap junction channels between exosomes and recipient cells, which facilitates transferring various TMZ resistance-related factors from exosomes to U251s cells.…”
Section: Discussionmentioning
confidence: 99%
“…U118MG, a WHO grade IV human GBM cell line, derived from highly malignant GBM tumors. U251 glioma cells are derived from a grade II neuroblastoma (3941). The morphology of U251 cells are epithelial, while the morphology of U118MG cells are mixed and both glioblastoma and astrocytoma cells are present (42, 43).…”
Section: Discussionmentioning
confidence: 99%